Impact of COVID-19 Pandemic on Respiratory Pathogen Epidemiology: An Eight-Years Retrospective Study - Elisa Zanotto; Francesca Sidoti; Alessandro Bondi; Antonio Curtoni; Giorgia Piccinini; Mattia Genco; Federica Zullo; Silvia Garazzino; Silvia Corcione; Paolo Solidoro; Rossana Cavallo; Cristina Costa (Sci)
Respiratory infections, particularly of the upper airways, play an important role in human pathologies, with them being the most common cause of disease in both children and adults, with a relevant impact on healthcare systems. Pathogen identification is particularly important in critical patients, with molecular assays being the most used methods. Herein, the molecular epidemiology of respiratory viruses in Northwestern Italy was studied by using an upper respiratory tract syndromic panel over a period of eight years, from January 2016 to December 2023, in order to evaluate the impact of the COVID-19 pandemic in this particular geographic area. Overall, over the study period, 22,270 tests were performed; in particular, 12,882 were performed in pediatric patients and 9388 in the adult population. Based on the analysis of the epidemiological trends, the complete disappearance of some viruses during the restriction periods was observed, as well as their resumption soon afterward; in particular, positive rates of Influenza A and B and Respiratory Syncytial Virus decreased at the end of 2020 and during 2021, whereas only Respiratory Syncytial Virus increased at the end of 2021. As expected, this study evidenced the relevant modifications that occurred in the typical epidemiology of respiratory viruses throughout the periods before, during, and after the COVID-19 pandemic and supported the role of syndromic panels in the diagnostic workflow of common respiratory infections.